2021
DOI: 10.3390/microorganisms9051066
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Engineered Commercial Chicken Line Is Resistant to Highly Pathogenic Avian Leukosis Virus Subgroup J

Abstract: Viral diseases remain a major concern for animal health and global food production in modern agriculture. In chickens, avian leukosis virus subgroup J (ALV-J) represents an important pathogen that causes severe economic loss. Until now, no vaccine or antiviral drugs are available against ALV-J and strategies to combat this pathogen in commercial flocks are desperately needed. CRISPR/Cas9 targeted genome editing recently facilitated the generation of genetically modified chickens with a mutation of the chicken … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Another problem in veterinary medicine is the avian leukaemia virus. In this Special Issue, Kheimar et al [ 8 ] showed that a genetically engineered chicken with original mutation of ALV-J receptor is resistant to Highly Pathogenic Avian Leukosis Virus Subgroup J, which can be useful for controlling this pathogen and improving poultry health in field conditions.…”
Section: Results and Progressmentioning
confidence: 99%
“…Another problem in veterinary medicine is the avian leukaemia virus. In this Special Issue, Kheimar et al [ 8 ] showed that a genetically engineered chicken with original mutation of ALV-J receptor is resistant to Highly Pathogenic Avian Leukosis Virus Subgroup J, which can be useful for controlling this pathogen and improving poultry health in field conditions.…”
Section: Results and Progressmentioning
confidence: 99%
“…In this study, we demonstrated that homozygous in vivo knock-out of the chicken tva gene by a frame-shifting deletion in the second exon results in complete resistance to two ALV subgroups, A and K, which share Tva as an entry receptor. After ALV-J, where the complete resistance was achieved by gene editing of the chicken Na + /H + exchanger 1 [30,34], it is the second example of artificial anti-viral resistance conferred by genetic manipulation of the chicken. In pigs, this strategy was employed for resistance to the porcine reproductive and respiratory syndrome virus and transmissible gastroenteritis virus by editing specific receptors CD136 [35] and pAPN [36].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have identified a novel ISG, ACSL1, that is important to inhibit ALV-J replication. Inhibition of virus replication in a host population can significantly reduce the change of viral adaption (44). The availability of genome-editing tools, notably CRISPR/Cas9, widens the scope of animal breeding and its applications in the context of disease control, while targeted genome editing has been proven useful to resistant ALV-J in chickens (34,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of virus replication in a host population can significantly reduce the change of viral adaption (44). The availability of genome-editing tools, notably CRISPR/Cas9, widens the scope of animal breeding and its applications in the context of disease control, while targeted genome editing has been proven useful to resistant ALV-J in chickens (34,44,45). In this context, exploiting more antiviral genes are particularly valuable in chickens.…”
Section: Discussionmentioning
confidence: 99%